Investigating the association between Candida albicans and early childhood dental caries: A comprehensive systematic review and meta-analysis. - Lusine G Khachatryan; Fatemeh Allahbakhsi; Diana E Vadiyan; Mahdi Mohammadian (PLoS ONE)
Background Early childhood caries (ECC) is a significant public health concern affecting children globally. Recent studies suggest a potential association between the presence of Candida albicans (C. albicans) in the oral cavity and the risk of ECC, but findings have been inconsistent. This systematic review and meta-analysis aimed to investigate the association between C. albicans and ECC. Methods A comprehensive literature search was conducted across databases including PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, Google Scholar, and Scopus. Studies were included if they examined the presence of C. albicans and the occurrence or severity of dental caries in children. Data extraction and quality assessment were performed independently by two reviewers. Statistical analyses, including pooled odds ratios (OR) and 95% confidence intervals (CI), were conducted to synthesize the findings. Results A total of 22 studies, involving 3301 participants, were included in the meta-analysis. The findings revealed a significant association between the presence of C. albicans and an increased likelihood of ECC, with a pooled odds ratio (OR) of 4.42 (95% CI: 3.14-6.24, p < 0.001). Subgroup analyses showed that factors such as geographic region, study design, and detection methods influenced the strength of this association. Studies conducted in Europe reported a stronger association (OR: 10.13, 95% CI: 6.01-17.09) compared to those in Asia (OR: 3.62, 95% CI: 2.53-5.20) and the Americas (OR: 3.98, 95% CI: 1.14-13.87). Case-control studies had a higher pooled OR (5.30, 95% CI: 1.72-16.31) compared to cross-sectional studies (4.30, 95% CI: 2.92-6.33). The odds of ECC in children with C. albicans were 4.08 (95% CI: 2.65-6.27) in dental plaque samples, 9.55 (95% CI: 2.17-42.01) in oral swab samples, and 4.70 (95% CI: 2.44-9.09) in saliva samples. No publication bias was observed based on Begg's test (P-value = 0.612) and Egger's test (P-value = 0.250). Conclusions The findings provide support for the hypothesis that C. albicans plays a role in the development of ECC. Moving forward, it is essential for future research to concentrate on comprehending the mechanisms that underlie this relationship and to develop specific strategies for prevention.